Pengaruh Kepuasan Kerja, Budaya Organisasi, dan Kecerdasan Emosional Terhadap Kinerja Karyawan - Dyah Muktiningtyas Sari; Suhana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to assess the influence of job satisfaction, organizational culture and emotional intelligence on employee performance. The research was conducted at GERAI INDOSAT OOREDOO SEMARANG using employees from the call center digital care division as samples. Convenience sampling was the method used to select samples. Data validity testing utilized factor analysis. Data analysis was performed using SPSS version 27.0 software. The research results indicate that job satisfaction significantly affects employee performance. Additionally, organizational culture also plays a role in influencing employee performance, and emotional intelligence also have a significant impact on employee performance. This study contributes both theoretically and practically.